THE CONFLICT BETWEEN MOSQUE MANAGEMENT BOARD AND COMMUNITIES: A Case Study of Conflict Between Asy Syifa Mosque Management Board and the Community in Singaran Pati District, Bengkulu City - Satria Wiranata; Akhmad Rifa'i (LISAN AL-HAL: Jurnal Pengembangan Pemikiran dan Kebudayaan, 2024)
The Mosque Management Board (MMB) is the driver of implementing a Mosque's activities. A mosque in a short time can lose its potential for usefulness if there is conflict. This study aims to explain the causes that triggered the conflict between the Asy Syifa Mosque Management Board and the Padang Nangka Village, Singaran Pati District, Bengkulu City community. This type of research is descriptive qualitative research. This data research uses observation techniques to directly gain community condition, situation, background, and behavior of people in Asy Syifa Board Management and the Communities. This research also uses Indepth interviews techniques to cover both side about the conflict happened. This means the interview set to Asy Syifa Mosque Board Management, the community which are residents of RT 01, RT 02, RT 03, RT 17, And the mediator appointed. Then, the data obtained is analyzed descriptively with Miles and Huberman narrative model. In this study, it was found that conflicts were caused by various disputes such as the election of new administrators, transparency of financial management, and important mosque decisions that did not go through deliberation. Another finding in this study is that there was a failed mediation effort because the community did not consider the appointed mediator neutral. With this research, it is hoped that the Mosque Management Board in Indonesia will resolve conflicts by involving third parties as mediators and be more open to suggestions and criticism given. After that, clean up and try to develop patterns of idarah (management), imarah (program management) and ri'ayah (physical management) to board members who will minimize conflict in the future.